2021
DOI: 10.1159/000514479
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Outcomes in Patients with Neurosarcoidosis

Abstract: <b><i>Introduction:</i></b> Audiovestibular symptoms are rare in sarcoidosis, but they may also be the first manifestation of the disease. Sudden or progressive bilateral hearing loss is usually associated with vestibular impairment. The mechanism of hearing loss remains unclear, but clinical presentation and magnetic resonance imaging suggest a retrocochlear site for the lesion in most patients. Several cases of hearing recovery after corticosteroid treatment have been reported. In pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…One study suggested waiting over a year to ensure that the hearing will not recover (2), but to remain vigilant and perform serial imaging as cochlear ossification has been reported in this group of patients. Overall, excellent CI outcomes are reported in several small studies in the context of neurosarcoidosis, and these outcomes were stable over time (2,25,52,70).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…One study suggested waiting over a year to ensure that the hearing will not recover (2), but to remain vigilant and perform serial imaging as cochlear ossification has been reported in this group of patients. Overall, excellent CI outcomes are reported in several small studies in the context of neurosarcoidosis, and these outcomes were stable over time (2,25,52,70).…”
Section: Discussionmentioning
confidence: 88%
“…Screening by title and abstract excluded 2,345 studies. Full-text review excluded 126 studies, and a total of 53 publications were included in the final analysis (2,5,6,8–10,15–61). A diagram of the search process can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%